HCI for peace: preventing, de-escalating and recovering from conflict - Hourcade, Juan Pablo; Bullock-Rest, Natasha E.; Davis, Janet; Jayatilaka, Lahiru; Moraveji, Neema; Nathan, Lisa P.; Zaphiris, Panayiotis (My University, 2012)
The increasing ubiquity of computing devices coupled with recent empirical research on the factors that affect the likelihood of conflict provide HCI researchers with new opportunities to conduct research on interactive systems designed to prevent, de-escalate and recover from conflict. Approaches used by HCI researchers in this field have included the use of a multi-lifespan research initiative to support peace and reconciliation after genocide, CSCW to facilitate communication, visualization to help detect landmines, and calming technology to support individuals desiring interactive systems that scaffold non-violent interactions. In this workshop we plan to further explore these ideas and discuss existing and future challenges.
Keywords: Cyprus; Calming technology; Landmines; Peace; Post-conflict reconciliation; Social media; Value sensitive design; War